The Power of Shopee Mall Branding in Reducing Counterfeit Risk and Increasing Purchase Intention Among Gen Z - Bella Hartati; Cucu Hodijah; Fatimah Abdillah (Journal of Management and Social Sciences, 2026)
The growth of e-commerce has made online marketplaces a major channel for purchasing fashion products, yet it has also increased consumer concerns about counterfeit goods, especially in shoes and sneakers. This study examines the role of Shopee Mall Signal Perception in increasing Purchase Intention for original shoes among Gen Z consumers by considering the mediating roles of Perceived Shopping Security and Decision Convenience. A quantitative explanatory approach was used, involving 239 Gen Z Shopee users in Indonesia selected through purposive sampling. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. The findings show that Shopee Mall Signal Perception positively affects Perceived Shopping Security (β = 0.430), Perceived Shopping Security improves Decision Convenience (β = 0.399), and Decision Convenience increases Purchase Intention (β = 0.359). Shopee Mall Signal Perception also has a direct effect on Purchase Intention (β = 0.182), while the serial mediation effect through Perceived Shopping Security and Decision Convenience is significant (β = 0.062). These findings imply that marketplace labels can function as authenticity signals that reduce uncertainty, simplify consumer decisions, and strengthen confidence in purchasing original products online.